2015
DOI: 10.1007/s40519-015-0199-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile and psychological variables after bariatric surgery: association with weight outcomes

Abstract: An association between metabolic and psychological variables, particularly concerning TG blood levels, disordered eating and psychological distress/depression was found. Only higher levels of disordered eating, TG and HbA_1c showed and independent correlation with less weight loss. Targeting maladaptive eating behaviors may be a reasonable strategy to avoid weight regain and optimize health status post-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 52 publications
1
7
0
6
Order By: Relevance
“…Considerable improvement of all lipid sub-fractions was observed during follow-up in our study, in line with other investigations[20,25,26]. The Swedish obese subject (SOS) study indicated that the incidence rate of hypertriglyceridemia was significantly lower in the surgically treated group than in the control group after two years[27].…”
Section: Discussionsupporting
confidence: 92%
“…Considerable improvement of all lipid sub-fractions was observed during follow-up in our study, in line with other investigations[20,25,26]. The Swedish obese subject (SOS) study indicated that the incidence rate of hypertriglyceridemia was significantly lower in the surgically treated group than in the control group after two years[27].…”
Section: Discussionsupporting
confidence: 92%
“…It could also be useful to assess impulsivity pre-operatively, though Sheets and colleagues [25] argue that especially post-operative variables seem to have an impact on weight loss outcome after bariatric surgery. Brandão and colleagues [27] hypothesized that impulsivity might be more associated with weight regain after surgery and not with weight loss. Thus, several post-operative measurement points concerning weight regain and weight loss outcomes should be completed.…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers [12,27] did not find a predictive value of impulsivity on EWL after bariatric surgery. Thus, Gerlach and colleagues [12] propose that pathological eating behavior might mediate the association between impulsivity and weight loss outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Eating behaviors is referred to as one of the components of weight management. In fact, psychological variables were reported to be associated with weight loss [7,8] . Clinical studies are limited using objective scores of eating behavior in association with weight management.…”
Section: Introductionmentioning
confidence: 99%